Move to strike - O'Shaughnessy, Perri (New York : Delacorte Press, 2000)
Nina's client is her son's best friend, Nikki Zack, a 16-year-old girl charged with murder. Nikki is accused of stealing from her uncle, a plastic surgeon, and killing him with an ancient samurai sword. Nina must pull an ace out of her sleeve in the courtroom to save her client.
Keywords: Women lawyers -- Fiction; Detective and mystery fiction